Treatment of Chalazian: a Comparative Cross-sectional Study - Bhattarai, Binita (Europasian Journal of Medical Sciences, 2019)
Introduction: Chalazion is a common eyelid margin disorder manifesting as granulomatous inflammation associated with meibomian gland lipids. There are three methods of treating chalazian: Intralesional Triamcinolone Acetonide (0.1-0.3 ml of 40mg/ml), Incision and Curettage and Conservative Treatment (hot compression +lid hygiene + antibiotic ointment). Methods: Patients with chalazian presenting to the Outpatient Department (OPD) of the Lumbini Eye Institute and Research Center (LEIRC) from 15 March 2017 to 15 July 2017 were included in the study. They underwent any of the three procedures (Conservative Treatment or Triamcinolone Acetonide Injection or Incision and Curettage) according to their choice. We compared all three methods of treatment of chalazion on follow up visit at 2 weeks, which was done to determine effectiveness in terms of reduction of size or complete resolution of the chalazia. Results: Out of 112 patients enrolled in study 65(58%) were females and 47(42%) were male with a male: female ratio of (0.7:1). The mean age of involvement was 25.7years (SD 10.3). At 2 weeks follow up there was complete resolution in incision and curettage (I and C) group 77 % (41/53) and in Triamcinolone Acetonide (TA) injection group 63 %( 20/32). Pearson’s correlations showed that I and C were superior to any other forms of intervention for any size of chalazian followed by intralesional injection of TA. Conclusion: Incision and Curettage remained the best choice for the treatment of chalazion followed by triamcinolone acetonide injection but may need multiple injections.